The neon hieroglyph / Tai Shani. - Shani, Tai, 1976- (Strange Attractor Press, 2022)
From the cellular to the galactic, via Paleolithic cave markings to the trace impressions left by drone photography on our mind's eye, incorporating dancing plagues, communist psychedelic witches, hyper-sexual fungi, chthonic descents, and skyward ascents, 'The Neon Hieroglyph' weaves together a series of painterly and poetic considerations on a feminised history of the rye fungus Ergot, the chemical basis of LSD.